A comparison of the modelled impacts on CVD mortality if attainment of public health recommendations was achieved in metropolitan and rural Australia. Issue 2 (13th August 2019) - Alston, Laura; Jacobs, Jane; Allender, Steven; Nichols, Melanie
Abstract: Objective: To (i) determine the proportion of deaths from CVD that could be avoided in both rural and metropolitan Australia if public health recommendations were met; (ii) assess the impact on the rural CVD mortality; and (iii) determine if policy priorities should be different by rurality for CVD prevention. Design: A macro-simulation modelling study of population data. Population, risk factor and CVD death data stratified by rurality were analysed using the Preventable Risk Integrated Model. The baseline scenario was the current risk factor levels (including physical activity, smoking, diet and alcohol). The counterfactual scenario was the population levels of these risk factors expected if public health recommendations were met. Setting: Metropolitan and rural Australia. Participants: Rural- and metropolitan-dwelling adults in Australia. Results: Both populations would experience similar relative declines in the proportion of deaths from CVD. A total of 14 892 deaths from CVD would be avoided annually; with similar declines in the proportions of deaths by rurality. Critically, the order of policy priorities for public health recommendation attainment would differ by rurality CVD prevention, with addressing fat intakes being a higher priority in rural areas. Conclusions: Achieving public health recommendations in Australia would result in large declines in CVD mortality. Despite declines in overall CVD mortality under this scenario, an inequality in CVD burden would persist for rural populations. The order of risk factor priorities would differ by rurality.